Liberalism in dark times the liberal ethos in the twentieth century - Cherniss, Joshua L. (Joshua Laurence), 1979- (Princeton University Press, 2021)
"Today, liberals face a predicament: how to defend liberal principles, when adherence to them seems to constitute a fatal disadvantage against unprincipled opponents. The challenge is not new. In the early years of the twentieth century, liberalism was attacked, by critics on both the right and, especially, the left for being hypocritical, naïve, irresponsible, and impotent. It couldn't, for example (anti-liberalists thought), address the acute inequality of imperial rule, racial segregation, and socio-economic poverty. These issues of social justice it was claimed by critics required a politics marked by an uncompromising commitment to ultimate ends, and an unrelenting use of power. Faced with such sentiments and the practical successes of anti-liberal ideologies (i.e. Fascism, Nazism, and Communism) liberals felt pressure to silence their scruples and doubts, and embrace the confidence, ruthlessness, and intransigence exhibited by their opponents. But doing so seemed tantamount to abandoning liberal hopes for, and commitments to, human freedom and all they valued in the first place. In Liberalism for Dark Times, Cherniss tells the story of the liberal response to this challenge in the twentieth century. Through a close study of five leading intellectuals engaged in these debates-Max Weber, Raymond Aron, Albert Camus, Reinhold Niebuhr, and Isaiah Berlin-Cherniss reconstructs a distinctive, neglected strand of liberal thought. This strand defines and defends liberalism as a political ethos: a complex of dispositions, temperament, and sensibility and style-which include skepticism; openness to experience; and careful, discriminating judgment-that shape how individuals make choices, meet challenges, understand and pursue possibilities, and conduct themselves toward others in the course of political struggle. In reconstructing the history of, what he calls, a tempered liberalism, and formulating it as a distinctive political perspective, Cherniss offers an alternative to the prevalent ways of thinking about both, liberalism's history and the intellectual resources available to it today"--